2021
DOI: 10.3390/medicina57101068
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Predictive Factors of COVID-19 Outcomes: A Retrospective Cohort Study in the Metropolitan Region of São Paulo (Brazil)

Abstract: Background and Objectives: The aim of this retrospective cohort study was to search individual, sociodemographic and environmental predictors of COVID-19 outcomes. Materials and Methods: A convenience sample of 1036 COVID-19 confirmed patients (3–99 years, mean 59 years; 482 females) who sought treatment at the emergency units of the public health system of Diadema (Brazil; March–October 2020) was included. Primary data were collected from medical records: sex, age, occupation/education, onset of symptoms, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…The factors associated with a higher probability of getting sick from COVID-19 among Gamarra workers were the infection of a family member, failure to comply with quarantine, foreign nationality, lack of sanitary services, and having a chronic disease in both the first and second waves. These findings are compatible with other studies conducted internationally (Oronce et al, 2020;Qiu et al, 2020;Amato et al, 2021;Doblhammer et al, 2021); however, these studies were conducted in the general population as the unit of analysis or with specific regions or areas of some countries. Some local studies have identified several factors related to increased mortality from COVID-19 (Hueda-Zavaleta et al, 2021;Yupari-Azabache et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The factors associated with a higher probability of getting sick from COVID-19 among Gamarra workers were the infection of a family member, failure to comply with quarantine, foreign nationality, lack of sanitary services, and having a chronic disease in both the first and second waves. These findings are compatible with other studies conducted internationally (Oronce et al, 2020;Qiu et al, 2020;Amato et al, 2021;Doblhammer et al, 2021); however, these studies were conducted in the general population as the unit of analysis or with specific regions or areas of some countries. Some local studies have identified several factors related to increased mortality from COVID-19 (Hueda-Zavaleta et al, 2021;Yupari-Azabache et al, 2021).…”
Section: Discussionsupporting
confidence: 91%